Improving Information System Audit Security through Artificial Intelligence (AI) Technology Integration - Fajrillah, Fajrillah; Hasyim Syarif, Shamir; Hiya, Nirmadarningsih (PT. Technology Laboratories Indonesia (TechnoLabs), 2025)
In today's digital age, information systems are the backbone of various organizations' operations, yet they are vulnerable to increasingly complex cybersecurity threats. Information system auditing plays a crucial role in ensuring system security and reliability, but conventional audit methods are beginning to face various limitations, particularly in handling large volumes of data and detecting threats quickly. This study aims to analyze the role, benefits, and challenges of integrating artificial intelligence (AI) technology into the information system audit process. Using a literature review method, this research found that AI can enhance audit effectiveness through data analysis automation, real-time fraud detection, and optimizing auditors' roles in strategic analysis. However, the implementation of AI still faces issues such as data quality, algorithm transparency, potential bias, auditor readiness, and the need for strong regulation and governance. This study recommends the need for synergy between technology, policy, infrastructure, and human resource competencies to ensure the effective and responsible implementation of AI in information system auditing in modern business environments.